KONTRIBUSI SEKTOR INDUSTRI PENGOLAHAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BERAU: KONTRIBUSI SEKTOR INDUSTRI PENGOLAHAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BERAU - Dandy Ahmad Drajat (ECO-BUILD, 2021)
The purpose of this research is to determine the contribution of the education service sector to the gross regional domestic product in Berau Regency, so that it can assist the Berau Regency government ini making programs and policies in the future. In this study using secondary data or publication data obtained from the Central Bureau of statistics of Berau Regency using data analysis, namely contribution analysis. With data for the 2015-2019 period of Berau Regency. The results of the study show that the influence of the manufacturing sector on Gross Regional Domestic Product in 2014 was 1.93 percent, while in 2015 there was an increase of 3.89 percent, in 2016 it decreased by 3.82 percent, in 2017 it again increased by 3.95 percent and in 2018 there was an increase in the contribution of 4.05 percent. Then in 2019 it decreased by 4.00 percent.